New insights linking Genetics with Eczema – Can Miasmatic Approach be a Possible Solution? (Homoeopathy for All, 2023)
Eczema (atopic dermatitis) is a  chronic inflammatory skin disease,  which is characterized by chronic  relapsing skin inflammation of  flexural areas of the body, severe itch,  and an aberrant immune response  to environmental allergens. In this  condition, an impairment of the skin  barrier is the main reason leading to  clinical manifestations such as marked  dryness, itching, sensitivity to external  irritants, and increased sensitivity to  bacterial and viral infections. There  has been a rising trend in the cases  of Eczema especially in India, in the  last four decades.1 It is noted that the  environmental factors along with the  genetic factors are the main causative  factors of the disease. Family and  twin studies revealed that up to 80%  of eczema susceptibility can be  linked to heritable factors, making  the genome the target of attention
Keywords: chronic; manifestations; bacterial